PENGARUH MODEL PEMBELAJARAN RADEC BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPTD SDN 014668 AIR GENTING T.A 2025/2026 - Ina Annafi’ah Telaumbanua; Lala Jelita Ananda; Winara; Imelda Free Unita Manurung; Waliyul Maulana Siregar (STKIP Subang, 2026)
This study aims to determine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model assisted by Wordwall media on the learning outcomes of fourth-grade students of UPTD SDN 014668 Air Genting in the academic year 2025/2026. This study is a quantitative study with a quasi-experimental method using a non-equivalent control group design. The population in this study were all fourth-grade students of UPTD SDN 014668 Air Genting, totaling 40 students. The sampling technique used saturated sampling, so that the entire population was used as a sample consisting of 20 students of class IV-B (experimental class) and 20 students of class IV-A (control class). The research instrument was a learning outcome test in the form of 20 multiple-choice questions that had been tested for validity, reliability, level of difficulty, and discriminatory power. Data collection techniques were carried out through tests, observations, documentation, and interviews. Data analysis techniques used normality tests, homogeneity tests, and hypothesis tests with t-tests (independent sample t-tests). The results showed that the average posttest score for the experimental class was 78, while the average score for the control class was 66.25. The results of the hypothesis test showed a significance value (Sig. 2-tailed) <0.05, so H₀ was rejected and Hₐ was accepted. This means that there is a significant effect of the use of the RADEC learning model assisted by Wordwall media on the science learning outcomes of fourth-grade students of UPTD SDN 014668 Air Genting in the 2025/2026 academic year